Prevalence of sleep-disordered breathing in the general population: the HypnoLaus study. Issue 4 (April 2015) - Heinzer, R; Vat, S; Marques-Vidal, P; Marti-Soler, H; Andries, D; Tobback, N; Mooser, V; Preisig, M; Malhotra, A; Waeber, G; Vollenweider, P; Tafti, M; et al.
Summary: Background: Sleep-disordered breathing is associated with major morbidity and mortality. However, its prevalence has mainly been selectively studied in populations at risk for sleep-disordered breathing or cardiovascular diseases. Taking into account improvements in recording techniques and new criteria used to define respiratory events, we aimed to assess the prevalence of sleep-disordered breathing and associated clinical features in a large population-based sample. Methods: Between Sept 1, 2009, and June 30, 2013, we did a population-based study (HypnoLaus) in Lausanne, Switzerland. We invited a cohort of 3043 consecutive participants of the CoLaus/PsyCoLaus study to take part. Polysomnography data from 2121 people were included in the final analysis. 1024 (48%) participants were men, with a median age of 57 years (IQR 49–68, range 40–85) and mean body-mass index (BMI) of 25·6 kg/m 2 (SD 4·1). Participants underwent complete polysomnographic recordings at home and had extensive phenotyping for diabetes, hypertension, metabolic syndrome, and depression. The primary outcome was prevalence of sleep-disordered breathing, assessed by the apnoea-hypopnoea index. Findings: The median apnoea-hypopnoea index was 6·9 events per h (IQR 2·7–14·1) in women and 14·9 per h (7·2–27·1) in men. The prevalence of moderate-to-severe sleep-disordered breathing (≥15 events per h) was 23·4% (95% CI 20·9–26·0) in women and 49·7% (46·6–52·8) in men. After multivariable adjustment, the upper quartile for the apnoea-hypopnoea index (>20·6 events per h) was associated independently with the presence of hypertension (odds ratio 1·60, 95% CI 1·14–2·26; p=0·0292 for trend across severity quartiles), diabetes (2·00, 1·05–3·99; p=0·0467), metabolic syndrome (2·80, 1·86–4·29; p<0·0001), and depression (1·92, 1·01–3·64; p=0·0292). Interpretation: The high prevalence of sleep-disordered breathing recorded in our population-based sample might be attributable to the increased sensitivity of current recording techniques and scoring criteria. These results suggest that sleep-disordered breathing is highly prevalent, with important public health outcomes, and that the definition of the disorder should be revised. Funding: Faculty of Biology and Medicine of Lausanne, Lausanne University Hospital, Swiss National Science Foundation, Leenaards Foundation, GlaxoSmithKline, Ligue Pulmonaire Vaudoise.